Secondary battery and preparation method thereof
By covering the modified zirconium oxide on the surface of the ternary layered oxide positive electrode material and covering the transition metal nanoparticles on the surface of the negative electrode, the problems of irreversible capacity loss and insufficient negative electrode kinetic performance during the first charge and discharge process are solved, and efficient first charge and discharge and magnification charge and discharge performance are achieved.
Patent Information
- Application Number
- CN202411806196.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-11
AI Technical Summary
In the prior art, layered oxide batteries have high irreversible capacity losses during the first charging and discharging process, and the kinetic performance of the negative electrode of traditional ion batteries is insufficient, which affects the rate charging and discharging capacity.
By covering the modified zirconium oxide on the surface of the ternary layered oxide positive electrode material, the oxygen vacancy lost by the material during the first charging process is compensated, and a small amount of transition metal nanoparticles are coated on the surface of the negative electrode to improve the transfer rate of lithium or sodium ions during the charging and discharging process.
The first charge and discharge efficiency and rate charge and discharge performance of layered oxide batteries are significantly improved, the irreversible capacity loss is reduced, and the energy density of the battery is improved.
Smart Images

Figure CN119601749A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, in particular to a secondary battery and a preparation method thereof. Background Art
[0002] In recent years, ternary layered nickel-cobalt-manganese oxide materials have become one of the preferred positive electrode materials for power batteries due to their high energy density and good cycle performance. Due to the limitation of lithium resources, layered oxide sodium electric materials have gradually become a research hotspot.
[0003] In the application of existing technologies, during the first charge and discharge process of layered oxides, part of the oxygen is released from the lattice, resulting in a high irreversible capacity loss. This irreversible capacity loss is mainly caused by the release of active substances in the form of "Li2O" or "Na2O" during the charging process, which results in the inability of the active substances to be completely embedded in the lattice during the discharge process.
[0004] In view of the above problems, one of the improvement methods in the prior art is to coat the surface of the layered materials. Although coating with materials such as AIPO4, FePO4, Al2O3, ZrO2, TiO2, etc. can improve the initial charge and discharge efficiency and reduce the irreversible capacity; however, it is difficult to completely retain the oxygen vacancies in the lattice through such coating, and the irreversible capacity cannot be completely eliminated.
[0005] In addition, application scenarios such as start-stop power supply require the battery to have excellent rate discharge performance. The negative electrode material is one of the key factors affecting the rate discharge performance. The conventional method mainly solves it by reducing the particle size of the negative electrode material, reducing compaction and surface density, and selecting new electrolytes. However, the above methods will increase the difficulty of trial production, extend the verification cycle, and most importantly, reduce the energy density of the battery.
[0006] Based on this, the present invention aims to improve the initial charge and discharge efficiency of layered oxide batteries and improve the kinetic performance of the negative electrode of traditional ion batteries, thereby improving the rate charge and discharge capacity of ion batteries. Summary of the invention
[0007] The object of the present invention is to provide a secondary battery which can effectively improve the initial charge and discharge efficiency and rate charge and discharge performance of a layered oxide type battery. At the same time, the present invention also provides a preparation method for preparing the secondary battery.
[0008] The first aspect of the present invention provides a secondary battery, which is composed of a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte, wherein:
[0009] The positive electrode material of the positive electrode sheet is composed of a positive electrode active main material and a modified zirconium oxide on its surface;
[0010] The negative electrode material of the negative electrode sheet consists of a negative electrode active main material and transition metal nanoparticles on its surface.
[0011] In the secondary battery, the chemical formula of the modified zirconium oxide is X-ZrO2;
[0012] In the chemical formula, X represents one element of Y, Pr, La, Ce, Sm, Nd, Eu, Gd, Mg, Ca, Sr, Ba, Al, K, and Na, or a compound composed of any two or more elements;
[0013] The mass ratio of X to ZrO2 is less than or equal to 10%, and the mass ratio of X-ZrO2 to the positive electrode material is 0.5-8%.
[0014] In the secondary battery, the positive electrode active main material is a ternary layered oxide;
[0015] The general chemical formula of the positive electrode material is X-ZrO2 / YNiZMnO;
[0016] In the general chemical formula, Y represents Li or Na; and Z represents any one of Cu, Fe and Co.
[0017] In the secondary battery, the negative electrode active main material is graphite or hard carbon.
[0018] In the secondary battery, in the transition metal nanoparticles, the transition metal is one element of Cu, Co, Ni, Cr, Mn, Fe, and Mo, or a combination of any two or more elements.
[0019] In the secondary battery, the particle size of the nanoparticles is 5-100 nm, and the mass of the nanoparticles accounts for 1-12% of the mass of the negative electrode active material.
[0020] A second aspect of the present invention provides a method for preparing a secondary battery, which is used to prepare the above-mentioned secondary battery, comprising the following steps:
[0021] Preparation of S1 cathode materials
[0022] Take a soluble salt containing X and Zr elements, add an organic solvent to dissolve it, and the amount of the organic solvent added is 1-20 times the volume of the pores of the soluble salt, to obtain a mixed solution 1; wherein X represents one element of Y, Pr, La, Ce, Sm, Nd, Eu, Gd, Mg, Ca, Sr, Ba, Al, K, Na, or a compound composed of two or more elements;
[0023] Add the positive electrode active material into the mixed solution 1 and stir evenly;
[0024] Dry the powder formed by stirring at a temperature of 80 to 120°C for 12 to 18 hours;
[0025] The dried powder is calcined in air at a temperature of 450 to 600° C. for 2 to 6 hours to obtain a positive electrode material powder;
[0026] Preparation of S2 positive electrode
[0027] Take the prepared positive electrode material powder, add N-methylpyrrolidone solvent, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride and mix evenly to obtain a second mixed solution; wherein the mass ratios of the positive electrode material powder, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride are 90-96%, 1.8-4.0%, 0.2-1.5%, and 2.0-4.5%, respectively;
[0028] The mixed solution 2 is coated on aluminum foil, the solid content of the coating slurry is 48-65%, and the positive electrode sheet is obtained by drying;
[0029] Preparation of S3 negative electrode material
[0030] Add water and dispersant to the negative electrode active main material, stir for 0.5 to 3 hours, and obtain a mixed solution 3, wherein the mass ratio of the dispersant to the negative electrode active main material is 1 to 8%;
[0031] Adding a transition metal salt solution to the mixed solution 3 and stirring for 0.5 to 2 hours, then adding a reducing agent and continuing stirring for 1 to 6 hours at a temperature of 70 to 120° C. to obtain a negative electrode material slurry containing transition metal nanoparticles, wherein the molar ratio of the reducing agent to the transition metal in the transition metal salt solution is 1 to 6;
[0032] The negative electrode material slurry is filtered, dried at a temperature of 60 to 120° C. for 3 to 10 hours, and then calcined at a temperature of 450 to 600° C. in a non-oxidizing atmosphere for 2 to 5 hours to obtain a negative electrode material powder;
[0033] Preparation of S4 negative electrode sheet
[0034] The prepared negative electrode material powder is added with deionized water, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber, and then coated on aluminum foil. The solid content of the coating slurry is 30-45%, and the negative electrode sheet is obtained by drying. The mass ratios of the negative electrode material powder, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber are 90-96%, 1.8-4%, 1.0-3% and 1.2-3% respectively.
[0035] Preparation of S5 battery cells
[0036] The prepared positive electrode sheet and negative electrode sheet are subjected to rolling, sheet cutting, sheet lamination, electrode ear welding, sealing, liquid injection, formation and capacity separation in sequence to obtain the secondary battery.
[0037] In the preparation method, the soluble salt containing X and Zr elements is one of carbonates, sulfates, acetates, oxalates, nitrates, hydroxylamine salts, nitrosamine salts, and acetylacetonate, or a combination of any two substances; the amount of organic solvent added is 1-20 times the water pore volume of the positive electrode active main material.
[0038] In the preparation method, the dispersant is one of polypropylene pyrrolidone, polyethylene glycol, polyvinyl alcohol, or a combination of any two substances.
[0039] In the preparation method, the reducing agent is one or a combination of any two of formaldehyde, formic acid, ascorbic acid, aniline, tyrosine, ethylene glycol, glycerol, isopropanol, and cyclohexanol.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] The preparation method of the present invention is simple. By coating the surface of the ternary layered oxide with modified zirconium oxide, the oxygen vacancies lost by the material during the first charging process are compensated based on the oxygen vacancies contained in the modified zirconium oxide, which greatly reduces the irreversible loss of active lithium or active sodium, thereby improving the first charge and discharge efficiency of the layered oxide type battery; in addition, by coating a small amount of transition metal nanoparticles on the surface of the negative electrode, the reduced metal nanoparticles have excellent catalytic ability, can reduce the reaction energy barrier, can accelerate the migration rate of lithium ions or sodium ions during the charge and discharge process, reduce the charge and discharge polarization, thereby improving the rate charge and discharge performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:
[0043] Figure 1 This is a rate discharge performance diagram of the batteries prepared in Examples 1 to 3 and Comparative Examples 2 and 3. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0045] The first embodiment of the present invention provides a secondary battery, which is composed of a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte. The positive electrode material of the positive electrode sheet is composed of a positive electrode active main material and modified zirconium oxide on its surface; the negative electrode material of the negative electrode sheet is composed of a negative electrode active main material and transition metal nanoparticles on its surface.
[0046] In a specific implementation, the chemical formula of the modified zirconium oxide is X-ZrO2;
[0047] In the chemical formula, X represents one element of Y, Pr, La, Ce, Sm, Nd, Eu, Gd, Mg, Ca, Sr, Ba, Al, K, and Na, or a compound composed of any two or more elements;
[0048] The mass ratio of X to ZrO2 is less than or equal to 10%, and the mass ratio of X-ZrO2 to the positive electrode material is 0.5-8%.
[0049] In a specific implementation, the positive electrode active main material is a ternary layered oxide;
[0050] The general chemical formula of the positive electrode material is X-ZrO2 / YNiZMnO;
[0051] In the general chemical formula, Y represents Li or Na; and Z represents any one of Cu, Fe and Co.
[0052] In a specific implementation, the negative electrode active main material is graphite or hard carbon.
[0053] In a specific implementation, in the transition metal nanoparticles, the transition metal is one element of Cu, Co, Ni, Cr, Mn, Fe, Mo, or a combination of any two or more elements.
[0054] In a specific implementation, the particle size of the nanoparticles is 5-100 nm, and the mass of the nanoparticles accounts for 1-12% of the mass of the negative electrode active material.
[0055] A second embodiment of the present invention provides a method for preparing a secondary battery, which is used to prepare the above-mentioned secondary battery, comprising the following steps:
[0056] Preparation of S1 cathode materials
[0057] Take a soluble salt containing X and Zr elements, add an organic solvent to dissolve it, and the amount of the organic solvent added is 1-20 times the volume of the pores of the soluble salt, to obtain a mixed solution 1; wherein X represents an element selected from Y, Pr, La, Ce, Sm, Nd, Eu, Gd, Mg, Ca, Sr, Ba, Al, K, and Na, or a compound composed of any two or more elements;
[0058] Add the positive electrode active material into the mixed solution 1 and stir evenly;
[0059] Dry the powder formed by stirring at a temperature of 80 to 120°C for 12 to 18 hours;
[0060] The dried powder is calcined in air at a temperature of 450 to 600° C. for 2 to 6 hours to obtain a positive electrode material powder;
[0061] Preparation of S2 positive electrode
[0062] Take the prepared positive electrode material powder, add N-methylpyrrolidone solvent, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride and mix evenly to obtain a second mixed solution; wherein the mass ratios of the positive electrode material powder, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride are 90-96%, 1.8-4.0%, 0.2-1.5%, and 2.0-4.5%, respectively;
[0063] The mixed solution 2 is coated on aluminum foil, the solid content of the coating slurry is 48-65%, and the positive electrode sheet is obtained by drying;
[0064] Preparation of S3 negative electrode material
[0065] Add water and dispersant to the negative electrode active main material, stir for 0.5 to 3 hours, and obtain a mixed solution 3, wherein the mass ratio of the dispersant to the negative electrode active main material is 1 to 8%;
[0066] Adding a transition metal salt solution to the mixed solution 3 and stirring for 0.5 to 2 hours, then adding a reducing agent and continuing stirring for 1 to 6 hours at a temperature of 70 to 120° C. to obtain a negative electrode material slurry containing transition metal nanoparticles, wherein the molar ratio of the reducing agent to the transition metal in the transition metal salt solution is 1 to 6;
[0067] The negative electrode material slurry is filtered, dried at a temperature of 60 to 120° C. for 3 to 10 hours, and then calcined at a temperature of 450 to 600° C. in a non-oxidizing atmosphere for 2 to 5 hours to obtain a negative electrode material powder;
[0068] Preparation of S4 negative electrode sheet
[0069] The prepared negative electrode material powder is added with deionized water, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber, and then coated on aluminum foil. The solid content of the coating slurry is 30-45%, and the negative electrode sheet is obtained by drying. The mass ratios of the negative electrode material powder, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber are 90-96%, 1.8-4%, 1.0-3% and 1.2-3% respectively.
[0070] Preparation of S5 battery cells
[0071] The prepared positive electrode sheet and negative electrode sheet are subjected to rolling, sheet cutting, sheet lamination, electrode ear welding, sealing, liquid injection, formation and capacity separation in sequence to obtain the secondary battery.
[0072] In the preparation method, the soluble salt containing X and Zr elements is one of carbonates, sulfates, acetates, oxalates, nitrates, hydroxylamine salts, nitrosamine salts, and acetylacetonate, or a combination of any two substances; the amount of organic solvent added is 1-20 times the water pore volume of the positive electrode active main material.
[0073] In the preparation method, the dispersant is one of polypropylene pyrrolidone, polyethylene glycol, and polyvinyl alcohol, or a combination of any two of the substances.
[0074] In the preparation method, the reducing agent is one of formaldehyde, formic acid, ascorbic acid, aniline, tyrosine, ethylene glycol, glycerol, isopropanol, and cyclohexanol, or a combination of any two of the substances.
[0075] For better understanding and implementation of the present invention, the present invention is further explained and illustrated below in conjunction with specific embodiments.
[0076] Example 1
[0077] A method for preparing a secondary battery comprises the following steps:
[0078] Preparation of S1 cathode materials
[0079] Take cerium oxalate, zirconium acetate and lanthanum acetate, the molar ratio of cerium to lanthanum is 1:1, the total mass of cerium oxide and lanthanum oxide accounts for 6% of zirconium oxide, add organic solvent ethanol to dissolve, the mass of ethanol is 3 times the total mass of cerium oxalate, zirconium acetate and lanthanum acetate, and obtain a mixed solution 1;
[0080] Add the positive electrode active main material sodium nickel cobalt manganate into the mixed solution 1, the mass of the sodium nickel cobalt manganate is 24 times that of the modified zirconium oxide, and stir evenly along the wall;
[0081] The stirred powder was left to stand for 24 hours and then dried at 100°C for 12 hours;
[0082] The dried powder was calcined in air at 450°C for 3 hours to obtain a positive electrode material powder;
[0083] Preparation of S2 positive electrode
[0084] Take the prepared positive electrode material powder, add N-methylpyrrolidone solvent, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride and mix evenly to obtain a mixed solution 2; wherein the mass ratios of the positive electrode material powder, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride are 95%, 2%, 0.5%, and 2.5%, respectively;
[0085] The mixed solution 2 is coated on aluminum foil, the solid content of the coating slurry is 58%, and the positive electrode sheet is obtained by drying;
[0086] Preparation of S3 negative electrode material
[0087] Add 2000 parts by weight of water and 4 parts by weight of dispersant polypropylene pyrrolidone to 200 parts by weight of hard carbon as the negative electrode active main material, and stir for 1 hour to obtain a mixed solution 3;
[0088] Add nickel nitrate and cobalt nitrate solutions to the mixed solution 3, the molar ratio of nickel to cobalt elements is 1:1, and the total mass of nickel and cobalt elements accounts for 8% of the hard carbon, and stir for 1 hour, then add the reducing agent ascorbic acid, the molar ratio of ascorbic acid to the transition metal is 2, and continue stirring for 3 hours at a temperature of 80°C to obtain a negative electrode material slurry containing nickel and cobalt nanoparticles;
[0089] The negative electrode material slurry was filtered, dried at 100° C. for 5 h, and then calcined at 450° C. in a non-oxidizing atmosphere for 3 h to obtain a negative electrode material powder;
[0090] Preparation of S3 negative electrode sheet
[0091] The prepared negative electrode material powder is added with deionized water, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber, and the mixture is evenly mixed, and then coated on aluminum foil, wherein the solid content of the coating slurry is 35%, and the negative electrode sheet is obtained by drying; wherein the mass ratios of the negative electrode material powder, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber are 94, 2%, 1.5% and 2.5% respectively;
[0092] Preparation of S4 battery cells
[0093] The prepared positive electrode sheet and negative electrode sheet are subjected to rolling, sheet cutting, sheet lamination, electrode ear welding, sealing, liquid injection, formation and capacity separation in sequence to obtain the secondary battery.
[0094] Example 2
[0095] A method for preparing a secondary battery comprises the following steps:
[0096] Preparation of S1 cathode materials
[0097] Take praseodymium acetate and zirconium acetate, the mass of praseodymium oxide accounts for 5% of zirconium oxide, add organic solvent ethylene glycol to dissolve, the mass of ethylene glycol is 4 times the total mass of praseodymium acetate and zirconium acetate, and obtain mixed solution 1;
[0098] Add the positive electrode active main material sodium nickel cobalt manganate into the mixed solution 1, the mass of the sodium nickel cobalt manganate is 18 times that of the modified zirconium oxide, and stir evenly along the wall;
[0099] The stirred powder was left to stand for 24 hours and then dried at 90°C for 15 hours;
[0100] The dried powder was calcined in air at 500°C for 2.5 hours to obtain a positive electrode material powder;
[0101] Preparation of S2 positive electrode
[0102] Take the prepared positive electrode material powder, add N-methylpyrrolidone solvent, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride and mix evenly to obtain a mixed solution 2; wherein the mass ratios of the positive electrode material powder, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride are 95%, 2%, 0.5%, and 2.5%, respectively;
[0103] The mixed solution 2 is coated on aluminum foil, the solid content of the coating slurry is 58%, and the positive electrode sheet is obtained by drying;
[0104] Preparation of S3 negative electrode material
[0105] 1500 parts by weight of water and 10 parts by weight of polyethylene glycol as a dispersant were added to 200 parts by weight of hard carbon as the negative electrode active main material, and stirred for 1.5 hours to obtain a mixed solution 3;
[0106] Add manganese nitrate and copper nitrate solutions to the mixed solution three, the molar ratio of manganese to copper elements is 1:1, and the total mass of manganese and copper elements accounts for 6% of the hard carbon, and stir for 0.5 hours, then add the reducing agent propylene glycol, the molar ratio of which to the transition metal is 3, and continue stirring for 4 hours at a temperature of 100°C to obtain a negative electrode material slurry containing manganese and copper nanoparticles;
[0107] The negative electrode material slurry was filtered, dried at 100° C. for 5 h, and then calcined at 500° C. in a non-oxidizing atmosphere for 2.5 h to obtain a negative electrode material powder;
[0108] Preparation of S3 negative electrode sheet
[0109] The prepared negative electrode material powder is added with deionized water, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber, and the mixture is evenly mixed, and then coated on aluminum foil, wherein the solid content of the coating slurry is 35%, and the negative electrode sheet is obtained by drying; wherein the mass ratios of the negative electrode material powder, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber are 94, 2%, 1.5% and 2.5% respectively;
[0110] Preparation of S4 battery cells
[0111] The prepared positive electrode sheet and negative electrode sheet are subjected to rolling, sheet cutting, sheet lamination, electrode ear welding, sealing, liquid injection, formation and capacity separation in sequence to obtain the secondary battery.
[0112] Comparative Example 1
[0113] A method for preparing a secondary battery, wherein the preparation methods of the negative electrode material, the negative electrode sheet and the battery cell are exactly the same as those in Example 1, except that the positive electrode material is not improved, and the commercially available sodium nickel cobalt manganese oxide in the prior art is directly used to prepare the positive electrode sheet.
[0114] Comparative Example 2
[0115] A method for preparing a secondary battery, wherein the preparation methods of the positive electrode material, the positive electrode sheet and the battery cell are exactly the same as those in Example 1, except that the negative electrode material is not improved, and the negative electrode sheet is directly prepared using commercial hard carbon in the prior art.
[0116] Comparative Example 3
[0117] A method for preparing a secondary battery is exactly the same as that of Example 1, except that the positive electrode material is not improved, and the positive electrode sheet is directly prepared using commercially available sodium nickel cobalt manganese oxide in the prior art; the negative electrode material is also not improved, and the negative electrode sheet is directly prepared using commercially available hard carbon in the prior art.
[0118] The first charge and discharge efficiency of the 1Ah batteries prepared in Examples 1, 2, 3 and Comparative Examples 1 and 3 was calculated when the batteries were divided into different capacities, and the data in Table 1 below were obtained:
[0119] Battery ID First charge and discharge efficiency (%) Example 1 98 Example 2 97 Example 3 99 Comparative Example 1 80 Comparative Example 3 78
[0120] Table 1 Summary of first charge and discharge efficiency
[0121] The 1Ah batteries prepared in Examples 1, 2, 3 and Comparative Examples 2 and 3 were subjected to 20C rate discharge test and 5C charge-discharge cycle test at 25°C. The 5C charge-discharge cycle capacity retention rate curve is shown in FIG. Figure 1 As shown, the 20C rate charge and discharge cycle capacity retention rate data is shown in Table 2 below:
[0122]
[0123] Table 2 Summary of 20C discharge retention rate and 5C discharge cycle retention rate
[0124] Based on this:
[0125] It can be seen from Table 1 that for the batteries prepared in Examples 1-3, after the surface of the positive electrode material is coated with modified zirconium oxide, the first charge and discharge efficiency is close to 100%; while the positive electrode materials of Comparative Examples 1 and 3 are not improved, and the first charge and discharge efficiency is relatively low after directly using commercial nickel cobalt manganese oxide, which is only about 80%. This indicates that after the surface of the positive electrode is coated with modified zirconium oxide, an appropriate amount of oxygen vacancies in the modified zirconium oxide can indeed make up for the irreversible loss of active sodium during the first charge and discharge process, thereby improving the first charge and discharge efficiency.
[0126] As can be seen from Table 2, the 20C discharge capacity retention rate of the batteries prepared in Examples 1-3 at room temperature reaches more than 85%, which is much better than that of Comparative Examples 2 and 3 (capacity retention rate is less than 60%), indicating that after a layer of transition metal nanoparticles is coated on the surface of the negative electrode material, the transition metal nanoparticles have excellent catalytic properties, which can reduce the reaction energy barrier and accelerate the migration rate of sodium ions during the charge and discharge process, thereby reducing polarization and showing excellent rate discharge performance.
[0127] Combination Figure 1 It can be seen from the middle curve that after 400 cycles of 5C high-rate charge and discharge, the capacity retention rate of the batteries prepared in Examples 1-3 (higher than 90%) is significantly better than that in Examples 2 and 3 (retention rate lower than 85%), further proving that the negative electrode surface coated with transition metal nanoparticles exhibits excellent rate charge and discharge performance.
[0128] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A secondary battery, which is composed of a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte, characterized in that: The positive electrode material of the positive electrode sheet is composed of a positive electrode active main material and a modified zirconium oxide on its surface; The negative electrode material of the negative electrode sheet consists of a negative electrode active main material and transition metal nanoparticles on its surface.
2. The secondary battery according to claim 1, characterized in that: The chemical formula of the modified zirconium oxide is X-ZrO2; In the chemical formula, X represents one element of Y, Pr, La, Ce, Sm, Nd, Eu, Gd, Mg, Ca, Sr, Ba, Al, K, and Na, or a compound composed of any two or more elements; The mass ratio of X to ZrO2 is less than or equal to 10%, and the mass ratio of X-ZrO2 to the positive electrode material is 0.5-8%.
3. The secondary battery according to claim 2, characterized in that: The positive electrode active main material is a ternary layered oxide; The general chemical formula of the positive electrode material is X-ZrO2 / YNiZMnO; In the general chemical formula, Y represents Li or Na; and Z represents any one of Cu, Fe and Co.
4. The secondary battery according to claim 1, characterized in that: The negative electrode active main material is graphite or hard carbon.
5. The secondary battery according to claim 1, characterized in that: In the transition metal nanoparticles, the transition metal is one element of Cu, Co, Ni, Cr, Mn, Fe, and Mo, or a combination of any two or more elements.
6. The secondary battery according to claim 1, characterized in that: The particle size of the nanoparticles is 5-100 nm, and the mass of the nanoparticles accounts for 1-12% of the mass of the negative electrode active material.
7. A method for preparing a secondary battery, characterized in that: The following steps are involved: Preparation of S1 cathode materials Take a soluble salt containing X and Zr elements, add an organic solvent to dissolve it, and the amount of the organic solvent added is 1-20 times the volume of the pores of the soluble salt, to obtain a mixed solution 1; wherein X represents one element of Y, Pr, La, Ce, Sm, Nd, Eu, Gd, Mg, Ca, Sr, Ba, Al, K, Na, or a compound composed of two or more elements; Add the positive electrode active material into the mixed solution 1 and stir evenly; Dry the powder formed by stirring at a temperature of 80 to 120°C for 12 to 18 hours; The dried powder is calcined in air at a temperature of 450 to 600° C. for 2 to 6 hours to obtain a positive electrode material powder; Preparation of S2 positive electrode Take the prepared positive electrode material powder, add N-methylpyrrolidone solvent, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride and mix evenly to obtain a second mixed solution; wherein the mass ratios of the positive electrode material powder, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride are 90-96%, 1.8-4.0%, 0.2-1.5%, and 2.0-4.5%, respectively; The mixed solution 2 is coated on aluminum foil, the solid content of the coating slurry is 48-65%, and the positive electrode sheet is obtained by drying; Preparation of S3 negative electrode material Add water and dispersant to the negative electrode active main material, stir for 0.5 to 3 hours, and obtain a mixed solution 3, wherein the mass ratio of the dispersant to the negative electrode active main material is 1 to 8%; Adding a transition metal salt solution to the mixed solution 3 and stirring for 0.5 to 2 hours, then adding a reducing agent and continuing stirring for 1 to 6 hours at a temperature of 70 to 120° C. to obtain a negative electrode material slurry containing transition metal nanoparticles, wherein the molar ratio of the reducing agent to the transition metal in the transition metal salt solution is 1 to 6; The negative electrode material slurry is filtered, dried at a temperature of 60 to 120° C. for 3 to 10 hours, and then calcined at a temperature of 450 to 600° C. in a non-oxidizing atmosphere for 2 to 5 hours to obtain a negative electrode material powder; Preparation of S4 negative electrode sheet The prepared negative electrode material powder is added with deionized water, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber, and then coated on aluminum foil. The solid content of the coating slurry is 30-45%, and the negative electrode sheet is obtained by drying. The mass ratios of the negative electrode material powder, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber are 90-96%, 1.8-4%, 1.0-3% and 1.2-3% respectively. Preparation of S5 battery cells The prepared positive electrode sheet and negative electrode sheet are subjected to rolling, sheet cutting, sheet lamination, electrode ear welding, sealing, liquid injection, formation and capacity separation in sequence to obtain the secondary battery.
8. The preparation method according to claim 7, characterized in that: The soluble salt containing X and Zr elements is one of carbonate, sulfate, acetate, oxalate, nitrate, hydroxylamine salt, nitrosamine salt, acetylacetonate, or a combination of any two substances; the amount of organic solvent added is 1-20 times the water pore volume of the positive electrode active main material.
9. The preparation method according to claim 7, characterized in that: The dispersant is one of polypropylene pyrrolidone, polyethylene glycol, polyvinyl alcohol, or a combination of any two of them.
10. The preparation method according to claim 7, characterized in that: The reducing agent is one of formaldehyde, formic acid, ascorbic acid, aniline, tyrosine, ethylene glycol, glycerol, isopropanol, and cyclohexanol, or a combination of any two of the substances.